ASPIRIN IN THE PREVENTION OF ATHEROTHROMBOSIS AND CORONARY HEART DISEASE - M. G. Bubnova (Российский кардиологический журнал, 2010)
This review is focused on the main aspects of aspirin therapy in the prevention of various atherothrombosis manifestations and coronary heart disease (CVD). The major mechanism of aspirin action is explained, and additional aspirin benefits, unrelated to its anti-aggregant activity, are described. Clinical groups in need for aspirin therapy, as a part of primary or secondary prevention, are specified, based on the evidence from large clinical trials. The benefits and risks of aspirin therapy are discussed.